A Review on the Factors Affecting the Learning of Arabic Macro-Skills Among Malay Undergraduate Students - Nurazan, Mohmad Rouyan; Siti Salwa, Mohd Noor; Aliyu, Abdullahi (2018)
This research intends to review a number of studies on the factors which might have an influence on the learning of Arabic as second language macro-skills (reading, writing, listening, and speaking) among Malay undergraduate students. The reviewed articles are categorised into four groups: literature related to factors affecting the speaking skills, literature related to factors affecting the writing skills, literature related to factors affecting the listening skills, and literature related to factors affecting the reading skills. However, different empirical studies reviewed confirm many factors have significant correlations with the students' performances in learning Arabic language macro-skills. Such factors are Malay students' attitude towards the Arabic language; the use of Arabic for communication purposes; lack of confidence and teaching techniques. However, some studies account different results. This mixture of results regenerates from diversities in methodology, variables used and the time of the study.